Arts de faire avec la vulnérabilité. Rencontres avec des coordonnateur.trice.s d’ULIS dans le cadre d’entretiens cliniques de recherche. - Konstantinos Markakis (Éducation et Socialisation)
Based on a psychoanalytically orientated clinical approach, the focus is on different ways of dealing with “vulnerability” in teaching situations that affects both the ULIS coordinator and the pupil. The analysis of three non-directive interviews highlights singular professional gestures that allow each one of the three coordinators to deal with vulnerability and discusses the links between these practices, the relation to knowledge and the "arts of doing in everyday life” (Certeau, 1990).